2014
DOI: 10.1080/10376178.2014.11081945
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the relationship between learning styles and academic performance among students in different nursing programs

Abstract: The results of this study can help educators devise classroom and clinical instructional strategies that respond to individual needs in order to maximize academic performance and enhance student success. A large sample is recommended for further research. Understanding the learning style preferences of students can enhance learning for those who are under performing in their academic studies, thereby enhancing nursing education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 1 publication
1
21
0
1
Order By: Relevance
“…4 Various studies investigated the relationship between learning styles and academic achievement in students of different disciplines. In some of these studies, a significant relationship was found between learning style and academic achievement, [8][9][10][11][12] while in some others, no significant relationship reported. 13,14 The current study was designed and conducted in light of the importance of knowledge of teachers about learners' learning styles, and contradictory results of different studies on the relationship between learning styles and academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…4 Various studies investigated the relationship between learning styles and academic achievement in students of different disciplines. In some of these studies, a significant relationship was found between learning style and academic achievement, [8][9][10][11][12] while in some others, no significant relationship reported. 13,14 The current study was designed and conducted in light of the importance of knowledge of teachers about learners' learning styles, and contradictory results of different studies on the relationship between learning styles and academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…34 One study did assess the academic performance of nursing students related to MBTI attributes. 35 There were no studies on the impact of MBTI on skills assessments. Waite and McKinney conducted the only study that leveraged the student's self-knowledge of personality type and applied it to a leadership development program in a nursing school.…”
Section: Resultsmentioning
confidence: 99%
“…El diagnóstico de los estilos de aprendizaje es de gran utilidad para implementar múltiples enfoques de enseñanza a partir de la diversidad, utilizando didácticas para responder a las necesidades de aprendizaje. Las evidencias sugieren que la planificación pedagógica basada en la diversidad de estilos de aprendizaje mejora el rendimiento académico (8,22), sobre todo, cuando se emplean varios enfoques de enseñanza en un programa de estudio; no obstante, no existen puntos finales respecto del efecto del manejo de didácticas específicas para cada estilo de aprendizaje (23) y se mantiene la recomendación de servirse de múltiples metodologías de enseñanza en un grupo de estudiantes.…”
Section: Discussionunclassified